The Embodiment of Intelligence: The Dawn of Physical AI - Florez, Hector; Garcia, Olmer (Revista Científica, 2026)
During the last decade, the world witnessed a digital cognitive revolution. In particular, the numerous large language models (LLMs) that have been recently developed now dominate text processing and image generation. Nevertheless, generative artificial intelligence (AI) cannot navigate physical systems with the same ease. For instance, generating an essay seems to be trivial for a modern model, but asking it to manipulate a delicate object still poses a serious challenge, illustrating Moravec's paradox: performing complex operations is easy for computers, but replicating human skills is very difficult.